(3QSGdI aj GdYbGbjQ hNhGUgGs
(3ChdgG (B:s
(3GdhQO hgh UfaGf CMeQ hCHjV hgh HGQO ai GdOQLI GdChdi jGHS GdHGHhfL hgh MGQ jGHS ai GdOQLI GdChdi dWja s
(3BNQgG (B:s
(3BNQ GdehLhO efgG Gdadad hgh jLH ef GQV GdgfO hgh MGQ jGHS ai GdOQLI GdQGHYI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGdKIs
(3HgG fXGe GdJYbjIHs
(3jdi GdeNWhW fbhd ef cdGe GdQGRi ef cJGHg GdeQTO hhUaGJ dJQcjH HYV GdCOhjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdWHs